2012
DOI: 10.7601/mez.63.217
|View full text |Cite
|
Sign up to set email alerts
|

Low-concentration copper solution jeopardizes larval movement and ability to survive predation: New insight into malaria eradication via vector control

Abstract: A new approach to eradicating malaria is urgently required. Emphasizing vector eradication via larval control, we tried to find a safe concentration of copper, which can be utilized to reduce larval survival. It has been observed that mosquito larvae died when exposed to solid copper in water. We confirmed this phenomenon in our own experiments. We next studied the minimum copper concentration for effectively killing or disturbing Anopheles stephensi larvae. A concentration of 0.6 ppm had a significant impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…In contrast, larvae tend to stay in a limited area. Our recent study on the ability of copper to kill or injure mosquito larvae (Reza et al, 2012) prompted us to utilize it in ovitraps. We examined the abilities of copper sulfate (CuSO 4 ) and solid copper (copper wire) to kill An.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, larvae tend to stay in a limited area. Our recent study on the ability of copper to kill or injure mosquito larvae (Reza et al, 2012) prompted us to utilize it in ovitraps. We examined the abilities of copper sulfate (CuSO 4 ) and solid copper (copper wire) to kill An.…”
Section: Introductionmentioning
confidence: 99%
“…LSM strategies also include the introduction of larvicide (chemical and biological agents) and larvivorous fish (natural predator) into larval habitats [57]. Previous studies have proposed the utility of using metallic [8, 9] and liquid [5, 10, 11] copper as a potential and affordable larvicide [7]. Copper is effective as a mosquito larvicide at a concentration below 2 ppm [9], the threshold value deemed safe for human drinking water [12], thus making copper a potential candidate for use in the public health setting.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings on the properties of copper to kill mosquito larvae [10] and laboratory testing on the effect of liquid copper at a concentration of 10 ppm on three species of mosquito larvae [11] prompted us to perform a field test in a malaria and dengue-endemic area of West Sumatra, Indonesia. Despite confirming the larvicide effect of copper [7], we observed that dilution by rainwater should be considered as confounding in the field since we noted that some larvae survived in outdoor ovitraps.…”
Section: Introductionmentioning
confidence: 99%
“…e lower concentration of 0.15 ppm seemed not to a ect the larvae, since the statistical analysis showed no signi cant di erence in capture-time compared to the control group. The highest concentration, 0.60 ppm, from the previous experiment (Reza et al, 2012) was not recommend to be used with Japanese medaka due to the high mortality rates of this sh at this concentration. ere is a small tolerance window in the survival rate of the sh treated in 0.26 ppm with the 0.30 ppm.…”
mentioning
confidence: 98%
“…Our previous study (Reza et al, 2012) showed that low concentrations of copper could kill larvae or at least jeopardized larval survival in the guppy (Poecilia reticulata). We are thinking of the possibility to combine copper treatment with the use of mosquito sh in the eld.…”
mentioning
confidence: 99%